2016
DOI: 10.1038/oncsis.2015.46
|View full text |Cite
|
Sign up to set email alerts
|

Energy disruptors: rising stars in anticancer therapy?

Abstract: The metabolic features of tumor cells diverge from those of normal cells. Otto Warburg was the first to observe that cancer cells dramatically increase their glucose consumption to generate ATP. He also claimed that cancer cells do not have functional mitochondria or oxidative phosphorylation (OXPHOS) but simply rely on glycolysis to provide ATP to the cell, even in the presence of oxygen (aerobic glycolysis). Several studies have revisited this observation and demonstrated that most cancer cells contain metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
104
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(108 citation statements)
references
References 90 publications
2
104
0
2
Order By: Relevance
“…However, therapeutic targeting of the Warburg effect in cancer cells has proven difficult, owing to their use of the same glycolytic enzymes as normal cells and the consequent risk of on-target adverse effects, as well as the expression of multiple isoforms of these enzymes (Hay, 2016; Vander Heiden and DeBerardinis, 2017). Although 2DG has been explored as a therapeutic agent (Landau et al, 1958; Raez et al, 2013), poor efficacy and undesired side effects such as hypoglycemia, fatigue, and tachycardia have limited its application as a single agent therapy (Bost et al, 2016). Interestingly, 2DG does seem to hold some promise in sensitizing cancer cells when used in combination with other pharmacological agents, such as Metformin (Cheong et al, 2011), Docetaxel (Raez et al, 2013), and BCL2 antagonists (Yamaguchi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, therapeutic targeting of the Warburg effect in cancer cells has proven difficult, owing to their use of the same glycolytic enzymes as normal cells and the consequent risk of on-target adverse effects, as well as the expression of multiple isoforms of these enzymes (Hay, 2016; Vander Heiden and DeBerardinis, 2017). Although 2DG has been explored as a therapeutic agent (Landau et al, 1958; Raez et al, 2013), poor efficacy and undesired side effects such as hypoglycemia, fatigue, and tachycardia have limited its application as a single agent therapy (Bost et al, 2016). Interestingly, 2DG does seem to hold some promise in sensitizing cancer cells when used in combination with other pharmacological agents, such as Metformin (Cheong et al, 2011), Docetaxel (Raez et al, 2013), and BCL2 antagonists (Yamaguchi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A direct consequence of this discovery is the development of therapeutic strategies that target glycolysis. 2-DG, the best known glycolysis inhibitor, has been shown to interfere with anabolic processes, disrupt antioxidant defenses and induce energy stress by blocking glycolysis [13]. However, 2-DG also has unanticipated side effects that remain to be deciphered.…”
Section: Discussionmentioning
confidence: 99%
“…First, it induces energy stress by depleting intracellular ATP [11,12]. Second, it affects anabolic processes by decreasing the production of glycolytic intermediates which are the precursors of nucleotides, lipids or proteins [13]. Finally, it results in NADPH deficiency and disrupts the antioxidant defenses of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that changes in cellular metabolism can alter the expression of specific microRNAs and promote epigenetic changes in tumor cells (Arora et al, 2015; Bishop and Ferguson, 2015; Chan et al, 2015). Although some of these interactions are mentioned above, in-depth discussions of all of the interactions that occur between cancer and metabolism are beyond the scope of this review and the reader is referred to a number of reviews on these subjects (Gatenby and Gillies, 2004; Vander Heiden et al, 2009; Cantor and Sabatini, 2012; Ward and Thompson, 2012; Semenza, 2013; Gaude and Frezza, 2014; Masson and Ratcliffe, 2014; Boroughs and DeBerardinis, 2015; Casey et al, 2015; Robey et al, 2015; Asati et al, 2016; Barron et al, 2016; Bost et al, 2016; Molon et al, 2016; Pavlova and Thompson, 2016; Pérez-Escuredo et al, 2016). The fact that metabolic dysregulation is seen in virtually all tumor cells has led to suggestions that a promising therapeutic strategy may be to exploit this feature.…”
Section: Tumor Metabolismmentioning
confidence: 99%